2021
DOI: 10.1186/s12903-021-01507-1
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries thresholds among adolescents in England, Wales, and Northern Ireland, 2013 at 12, and 15 years: implications for epidemiology and clinical care

Abstract: Background Dental caries is the most prevalent condition globally. Despite improvements over the past few decades, there remains a significant disease burden in childhood. Epidemiological surveys provide insight to disease patterns and trends, and have traditionally focused on obvious decay which are inconsistent with contemporary clinical criteria. This study examined the distribution of dental caries in 12- and 15-year-olds in England, Wales and Northern Ireland, by severity threshold, at sur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 25 publications
3
30
1
5
Order By: Relevance
“…The highest prevalence of dental caries of occlusal surfaces was in the lower first molar at baseline and at follow-up. First and second molars overall have a high risk for dental caries, and the prevalence of dental caries in occlusal surfaces is higher than that in proximal surfaces [36][37][38][39][40]. The trend in the present study was supported by these previous reports.…”
Section: Discussionsupporting
confidence: 89%
“…The highest prevalence of dental caries of occlusal surfaces was in the lower first molar at baseline and at follow-up. First and second molars overall have a high risk for dental caries, and the prevalence of dental caries in occlusal surfaces is higher than that in proximal surfaces [36][37][38][39][40]. The trend in the present study was supported by these previous reports.…”
Section: Discussionsupporting
confidence: 89%
“…A significant association was found between high DFA and poor oral health-related quality of life (OHRQoL), a multidimensional measure evaluating oral health status and its related functional and psychosocial impacts [ 87 ], in children [ 88 , 89 , 90 , 91 , 92 ] as well as adults [ 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. Significant relationships were also reported between high levels of DFA and measures of poor oral health (e.g., caries experience, gingival health, and toothbrushing frequency) in children [ 3 , 5 , 6 , 7 , 17 , 50 , 51 , 53 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ] and adults [ 4 , 61 , 65 , 66 , 93 ,…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen articles examined the relationship between oral health and dental attendance ( n = 4 pediatric, n = 14 adult). In children, irregular dental attendance was associated with DMFT [ 7 , 122 , 206 ] and poor OHRQoL [ 207 ]. In 13 studies of adults, irregular dental attendance was associated with poor oral health (e.g., DMFT and self-report of poor oral health) [ 8 , 56 , 66 , 96 , 100 , 125 , 135 , 160 , 167 , 169 , 171 , 208 , 209 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to Petersen et al [ 3 ], the reason could be due to parents’ unawareness of oral health, lower education level, and relatively low-income family income; it is also possible that children are afraid of dental treatment, thus concealing the symptoms or not cooperating with the dentist. Researches have demonstrated that pit and fissure sealant can effectively prevent caries [ 26 ] and is closely related to the prevalence of caries among children aged 6–17 years old [ 27 ]. This survey showed that the caries filling rate and pit and fissure sealant rate in São Tomé Island were both at a low level, indicating that strengthening oral health education, implementing oral health promotion to schools, improving oral health care knowledge, and popularizing caries preventing measures are necessary.…”
Section: Discussionmentioning
confidence: 99%